Injectable, Adhesive, and Self-Healing Composite Hydrogels Loaded With Oxybutynin Hydrochloride for the Treatment of Overactive Bladder in Rats - Sun, Peng; Wang, Zheng; Wu, Tong; Zuo, Shishuai; Huang, Xiaoyu; Cui, Zilian; Zhang, Dong (Frontiers in Bioengineering and Biotechnology, 2022)
Thirty SD rats were randomly divided into control group, model group, obfuscinin sustained release tablet group, obfuscinin hydrochloride solution group and obfuscinin hydrochloride hydrogel group. The uv absorption of OXY in the solution was detected by uv spectrophotometer at 233 nm, and the cumulative drug release was calculated by Origin software. The adhesion ability of L929 mouse fibroblasts to OCP50 and OCP100 hydrogels was tested. Cell density and cell elongation were observed by rhodamine staining. Cck-8 method and urodynamic examination were performed. The relative expression levels of Orai1 and STIM1 were detected by WB and QPCR. Ft-ir and NMR spectra showed that Dex was oxidized to PDA with aldehyde group. After loading OXY, the wet shear adhesion of OCP50 and OCP100 was higher than that of CP50 and CP100 (P<0.05), which were suitable for vaginal administration. Oxybutynin rapidly releases hydrogel in clean H, and the release slope becomes smaller and the release rate decreases by 20 h. Compared with the control group, CP50, CP100, OCP50 and OCP100 cells in the experimental group were expanded more. Compared with blank group, OCP50, CP100 and OCP100OD values of experimental group were higher, and cell survival rate was higher (P<0.05). Compared with the control group, the bladder space time in model group was shortened (P<0.05), the bottom bladder pressure was decreased, the urination threshold was increased (P<0.05), and the mean detrusor pressure was increased (P<0.05). Compared with the control group, the expression of Orail mRNA and STIM1 in model group, oxybutynin sustained-release tablet group and oxybutynin hydrochloride solution group were increased (P<0.05). Compared with the model group, the expression of Orail mRNA, STIM1 protein and mRNA in the obbussinine sustained-release tablet group, obbussinine hydrochloric acid solution group and obbussinine hydrogel group were decreased (P<0.05). We hypothesized that oxybutynin hydrogel mediated Ca2+ entry by increasing the expression of Orail mRNA and STIM1 mRNA and protein in overactive bladder (OAB) rats.